Hatchings (Book collections on Project MUSE., 2006)
It is New Year in Bulawayo, and anybody who is anybody is out celebrating. Hatchings, with an introduction by Khombe Mangwanda, was chosen by Professor Anthony Chennells in the Times Literary Supplement as his choice for the most significant book to have come out of Africa. "The story is simple. In a sentence it can be described as a love story centered on a young couple who discover the true power of love amid the social, economic and moral decay that threatens to swallow their love and everything else. But to say Hatchings is merely a love story would be criminal. It is more than that. Hatchings is a story about Bulawayo, about Zimbabwe, about corruption and cultural decay. In Hatchings John Eppel spares no one. With his sharp and yet witty pen he exposes corruption and pokes fun at those that are abusing power and this means literally everyone. Rich, poor, white, black, Indian, foreigner or local."--Raisedon Baya, Sunday News, Zimbabwe.